2012
DOI: 10.4155/fmc.12.99
|View full text |Cite
|
Sign up to set email alerts
|

Recent Work In The Development And Application Of Protein–Peptide Docking

Abstract: Interest in the development of novel peptide-based drugs is growing. There is, thus, a pressing need for the development of effective methods to enable novel peptide-based drug discovery. A cogent case can be made for the development and application of computational or in silico methods to assist with peptide discovery. In particular, there is a need for the development of effective protein-peptide docking methods. Here, recent work in the area of protein-peptide docking method development is reviewed and seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…A comparison of the results shown in Table 2 (a summary of results using recently developed protein-peptide docking methods) from ref. [19] showed that PaFlexPepDock was better than some of other docking protocols in terms of the Ave_rmsd. But it was worse than some methods on P(LE), it is our future working to improve it.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of the results shown in Table 2 (a summary of results using recently developed protein-peptide docking methods) from ref. [19] showed that PaFlexPepDock was better than some of other docking protocols in terms of the Ave_rmsd. But it was worse than some methods on P(LE), it is our future working to improve it.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the scoring problems and search problems are two basic and important considerations for understanding protein-peptide docking [3]. From the modeling perspective, the problem of flexibility is an un-solved problem for conventional protein docking algorithms [4].…”
Section: Introductionmentioning
confidence: 99%
“…The most common ones involve (i) a systematic search (e.g., exhaustive search, ensemble-based search, fragment-based search) or (ii) a stochastic search (e.g., Monte Carlo, evolutionary algorithm, swarm optimization, tabu search) [2], [5], [10]. Large ligands and peptides represent bigger challenges for docking, which might exceed the capabilities of many current approaches [11]- [15]. The treatment of ligand flexibility has been extensively reviewed elsewhere [2], [5], [10] and will not be specifically discussed here.…”
Section: Introductionmentioning
confidence: 99%
“…In this present study, DockQ (Basu & Wallner, 2016) was used to calculate the backbone RMSD of the peptide in native versus docked complex. The predicted pose is considered to be near-native if the backbone RMSD with respect to the native structure is ≤2.5 Å (Audie & Swanson, 2012). The success rate of the protocol was calculated by the F I G U R E 1 Flowchart describing the modified protocol for peptide modeling and ensemble docking number of predicted conformation cases that are near-native to the 53 native protein-peptide complexes in the LEADS-PEP dataset.…”
Section: Criteria For Evaluation Of Benchmarking Datasetsmentioning
confidence: 99%